2017
DOI: 10.1016/j.foodchem.2016.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Analytical optimization of a phenolic-rich herbal extract and supplementation in fermented milk containing sweet potato pulp

Abstract: The aims of the present study were to optimize and characterize the phenolic composition of a herbal extract composed of green mate (Ilex paraguariensis), clove (Syzygium aromaticum), and lemongrass (Cymbopogon citratus) and to propose the addition of this polyphenol-rich extract to fermented milks (FM) with/without sweet potato pulp (Ipomoea batatas). Proximate composition, pH, acidity, instrumental texture profile, total phenolic content (TPC), antioxidant activity (AA) of all formulations were measured, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 34 publications
5
30
0
1
Order By: Relevance
“…; Ramos et al . ; Helal and Tagliazucchi ) who highlighted a positive correlation between fermented products fortified with vegetables and antioxidant activity. Significant differences in the antioxidant activity were found among the kefir samples as a function of the type of added flavouring ( P < 0.05; Table ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Ramos et al . ; Helal and Tagliazucchi ) who highlighted a positive correlation between fermented products fortified with vegetables and antioxidant activity. Significant differences in the antioxidant activity were found among the kefir samples as a function of the type of added flavouring ( P < 0.05; Table ).…”
Section: Resultsmentioning
confidence: 97%
“…; Ramos et al . ; Helal and Tagliazucchi ) who showed that the addition of natural herbal extract to fermented milk increased the phenolic content of these dairy products. Furthermore, RK showed a higher capacity than HK (7.28 vs 5.91 mg GAE/100 g; P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…During the same refrigeration period, the IC 50 values of BFY scavenging DPPH, ABTS, and OH radical were meaningfully ( p < 0.05; p < 0.01) lower than those of the control, that meant, the antioxidant activity was significantly higher than that of the control. Therefore, like other antioxidant plant extracts, blueberry flower pulp could enhance the antioxidant activity of yogurt (Granato, Santos et al, ; Najgebauer‐Lejko et al, ; Ramos et al, ). The antioxidant activity of BFY was higher than hickory‐black soybean yogurt (Ye et al, ), and it mainly attributed to the phenolic compounds which came from blueberry flower pulp.…”
Section: Resultsmentioning
confidence: 99%
“…Plant extracts were also added to yogurt, and their effects on yogurt were evaluated. Multiple research results have indicated that the use of herbal preparations (basically aqueous extracts) not only increases the bioactive compounds and antioxidant activity of yogurts and fermented milks, but also increases considerably the sensory acceptance of these new fermented dairy products (Granato, Santos et al, ; Ramos et al, ). Yogurt that enhanced with peppermint, dill, basil, green mate, clove, and lemongrass extracts had faster rates of pH reduction than plain yogurt (Amirdivani & Baba, ; Ramos et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation